2010
DOI: 10.5664/jcsm.27820
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Positional Therapy to CPAP in Patients with Positional Obstructive Sleep Apnea

Abstract: Study Objectives: We hypothesized that positional therapy would be equivalent to continuous positive airway pressure (CPAP) at normalizing the apnea-hypopnea index (AHI) in patients with positional obstructive sleep apnea (OSA). Methods: Thirty-eight patients (25 men, 49 ± 12 years of age, body mass index 31 ± 5 kg/m 2 ) with positional OSA (nonsupine AHI < 5 events/h) identified on a baseline polysomnogram were studied. Patients were randomly assigned to a night with a positional device (PD) and a night on CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(77 citation statements)
references
References 16 publications
3
69
0
5
Order By: Relevance
“…This finding might be explained by the fact that in the supine position upper airway dimensions present increased propensity of collapse (Walsh et al, 2008). In this regard, it is not surprising that positional therapy has proven to be equivalent to continuous positive airway pressure at normalizing AHI in patients with positional OSA (Permut et al, 2010). However, even in patients with non-positional OSA, as were the apnoeic patients of the current study, positional dependence of snoring appears to persist.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This finding might be explained by the fact that in the supine position upper airway dimensions present increased propensity of collapse (Walsh et al, 2008). In this regard, it is not surprising that positional therapy has proven to be equivalent to continuous positive airway pressure at normalizing AHI in patients with positional OSA (Permut et al, 2010). However, even in patients with non-positional OSA, as were the apnoeic patients of the current study, positional dependence of snoring appears to persist.…”
Section: Discussionmentioning
confidence: 52%
“…The positional dependence of OSA is explained by the fact that turning from the lateral to supine position can lead to a decrease and an eventual collapse of the upper airway (positional OSA patients; Pevernagie et al, 1995). In these patients positional therapy has proven to be an effective alternative to continuous positive airway pressure therapy (Permut et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these more recent studies fall into many of the traps of prior research, generally being short term, 36,39,40,46,[49][50][51][52] failing to compare different treatment approaches, or using sample sizes inadequate to detect clinically meaningful differences. [52][53][54][55] In one larger and longer randomized trial, in which 723 nonsomnolent patients with OSA were randomized either to CPAP (N 5 357) or no active treatment (N 5 366) over a median of 4 years of follow-up, no intergroup difference was detected in the incidence of hypertension or other cardiovascular events. 56 And in another randomized trial comparing nasal CPAP and an oral appliance over 12 months, though AHI scores improved from baseline in both treatment groups, there was no difference between them, except that more subjects withdrew from the nasal CPAP treatment arm due to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The present device circumvents this problem, as this small, light and comfortable-to-wear device does not cause any discomfort during position change. Permut et al (2010) showed recently that positional therapy with a bulky mass strapped to the back was equal to CPAP in normalizing the AHI in patients with a mild to moderate POSAS. However, patient selection criteria and thus definition of POSAS were not the same as in our study.…”
Section: Discussionmentioning
confidence: 99%